Two new species and new records of biting midges of the genus Culicoides from northwestern Argentina (Diptera: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2013)
The following two new species of Culicoides from the Argentinean Yungas are described, illustrated and placed to subgenus or species group and compared with related congeners: Culicoides calchaqui Spinelli & Veggiani Aybar and Culicoides willinki Spinelli & Veggiani Aybar. Culicoides daedaloides Wirth & Blanton is recorded for the first time for Argentina and Culicoides pseudoheliconiae Felippe-Bauer is firstly mentioned from the northwestern region of the country.